2018
DOI: 10.3390/agronomy8080152
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Carbon Dioxide, and Pest Biology, Managing the Future: Coffee as a Case Study

Abstract: The challenge of maintaining sufficient food, feed, fiber, and forests, for a projected end of century population of between 9-10 billion in the context of a climate averaging 2-4 • C warmer, is a global imperative. However, climate change is likely to alter the geographic ranges and impacts for a variety of insect pests, plant pathogens, and weeds, and the consequences for managed systems, particularly agriculture, remain uncertain. That uncertainty is related, in part, to whether pest management practices (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 117 publications
0
25
0
3
Order By: Relevance
“…Integrated Pest Management (IPM) is a strategy that encourages the reduction of pesticide use by employing a variety of nonchemical pest control methods to contain or manage pests below their economic injury levels [1]. The IPM programs implemented in various countries utilize all possible control strategies, including biological, cultural, chemical and ecosystem health techniques with the goal of reducing purchased inputs while maintaining the crop yield, its quality and profits [2][3][4]. The beginnings of integrated pest management took place in the United States in the 1960s as a response to the emerging environmental problems associated with the use of large amounts of chemical plant protection products [5].…”
Section: Introductionmentioning
confidence: 99%
“…Integrated Pest Management (IPM) is a strategy that encourages the reduction of pesticide use by employing a variety of nonchemical pest control methods to contain or manage pests below their economic injury levels [1]. The IPM programs implemented in various countries utilize all possible control strategies, including biological, cultural, chemical and ecosystem health techniques with the goal of reducing purchased inputs while maintaining the crop yield, its quality and profits [2][3][4]. The beginnings of integrated pest management took place in the United States in the 1960s as a response to the emerging environmental problems associated with the use of large amounts of chemical plant protection products [5].…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effect of pest infestation is extremely detrimental to coffee farmers, resulting in an average economic loss of yield of around 2 to 20% annually. .Previous work and Limitations Extensive studies have stated that more than 850 different kinds of insects have been found to attack coffee, out of which the cof-fee leaf miner, the coffee berry borer and the coffee White Stem Borer are the most prominent (Ziska, 2018). All previous stud-ies have primarily dealt with the detailed study of the infestation causes and effects, and subsequently preventive and management measures to ensure reduction in loss of yield.…”
Section: ---------------------------mentioning
confidence: 99%
“…Evidence suggests that recent shifts in climate have already affected the distribution and biology of disease and pest species of coffee (Ziska et al 2018). Thus, in recent years, the use of pesticides in Brazil has increased, turning the country the largest consumer of agrochemicals in the world (Pignati et al 2017).…”
Section: Introductionmentioning
confidence: 99%